SISTEM PENDUKUNG KEPUTUSAN PEMILHAN CALON PERANGKAT DESA TAPIAN NAULI KECAMATAN LINTONG NIHUTA DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Sarah Afriani Sihombing; Jijon Raphita Sagala (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2020)
Village officials who carry out most of the tasks of village heads carried out by village officials are those who assist the Village Head in implementing good governance with village officials who are able to work closely with the village head to advance good human resources. Village officials are important in the village in serving the community. Currently, in Tapian Nauli village, the selection of candidates for the village apparatus is still manual so that services to the community will be hampered. Until now there has not been an effective selection of candidates for village officials for the selection of candidates for the village apparatus Tapian Nauli. Buts Nauli. This system was built using the Additive weighting method so that a simple program that can be done more effectively. Additive weighting simple method one of the methods used in the decision support system with the calculation process by finding the weight value or suitability assessment for each attribute.